Per-Ventricular Insertion of Melody Valve-in-Valve in the Neoaortic Position in a Single-Ventricle Patient. Issue 1 (January 2018) - Clarke, Nicholas S.; El-Said, Howaida; Lamberti, John J.; Murthy, Raghav A.
Percutaneous therapies for congenital heart disease have been evolving rapidly despite limited investment from industry. The Melody transcatheter pulmonary valve (Medtronic, Inc, Minneapolis, MN USA) replacement therapy represents an important advancement in this arena. It has been approved in the United States for use in the pulmonary position, on a Humanitarian Device Exemption status. Off-label use of the Melody transcatheter pulmonary valve has extended to the mitral, pulmonary, and aortic valves, especially in previously implanted valves with prosthetic valve degeneration. The single-ventricle patient poses additional challenges. However, there exists one report in the English literature of a patient undergoing Melody transcatheter neoaortic valve replacement after the patient developed severe neoaortic regurgitation after Fontan palliation. Here, we describe a patient with hypoplastic left heart syndrome, palliated with a Norwood modified Blalock-Taussig shunt, with a progressively regurgitant quadricusp neoaortic valve who underwent bioprosthetic valve replacement. There was early prosthetic valve degeneration after a year of bioprosthesis implantation. As he was declined for transplantation, he underwent successful perventricular Melody valve-in-valve replacement.